31st Annual IAMSLIC Confrerence - Food and Agricultural Organization of the United Nations; Global Partner for Responsible Fisheries (Rome : FAO)
This CD contains all the papers presented at the 31st Annual IAMSLIC (International Association of Marine and Aquatic Science Libraries and Information Centers) Conference held in Rome, Italy, October 10-14, 20 05. The papers are in PDF format which were created in Adobe Acrob at version 7 and are most easily read using Acrobat. This CD does cont ain the Adobe Acrobat 7 Reader if you do not already have it on your co mputer. Choose from PC or Mac versions in the folder labeled Acrobat R eader. To access the papers, open the Table of Contents file. Click on the title of the paper or page you want to view and it will open in a new window. The Table of Contents file will remain open if you are using Acrobat 7. Using Acrobat 6 the papers do not open in a new windo w and you will have to open the Table of Contents file each time you wa nt to access a new paper.
With compliments of Fisheries Branch Library
Hardware needed: Mac 10 or higher, Windows.
CD-ROM drive
Keywords: Fisheries -- Research